2020
DOI: 10.3390/app10144734
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Properties of Concrete in Dry Environments with Different Curing Temperatures

Abstract: This paper investigated the fracture properties of concrete in dry environments with different curing temperatures (5, 20, 40, and 60 °C). For each curing condition, the key fracture parameters of concrete were tested using wedge splitting specimens at five different ages (3, 7, 14, 28, and 60 d). The results show that in dry environments, the effective fracture toughness and fracture energy of concrete exposed to elevated temperatures increased at a relatively high growth rate at an early age. Neverth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…cylinders, or 20 in. beams in the dimensions of 150 by 150 mm with a minimum length of 530 mm), temperatures, curing durations, and material strength development [15]. However, some of the multiple influence factors (a.k.a., independent variables) affect each other, which increases the complexity of the method selection [7].…”
Section: Anova [12]mentioning
confidence: 99%
“…cylinders, or 20 in. beams in the dimensions of 150 by 150 mm with a minimum length of 530 mm), temperatures, curing durations, and material strength development [15]. However, some of the multiple influence factors (a.k.a., independent variables) affect each other, which increases the complexity of the method selection [7].…”
Section: Anova [12]mentioning
confidence: 99%
“…However, this approach is not very economical or ecological, since it would require large ovens at the construction site or plant to heat the reinforcing cages. If the curing is performed within the concrete matrix, this approach would also require the heating of the whole concrete element, requiring a lot of energy and possibly influencing the concrete hydration reaction [72,73]. Therefore, alternative curing methods that enable a comparatively easy curing of large-scale elements on site, preferably by only heating the reinforcement within the concrete matrix, are needed.…”
Section: Thermoset Preimpregnated Textile Reinforcementsmentioning
confidence: 99%
“…Mi et al [3] investigated the fracture properties of concrete in dry environments with different curing temperatures (5, 20, 40, and 60 • C) and concluded that the optimum temperature suitable for the development of concrete fracture properties under dry conditions was around 40 • C. Bruno et al [4] compared the stress effects developed on the periodontal ligaments and using three different types of mandibular advancement devices (MADs) using finite element method (FEM) analysis. This research concluded that devices with a bilateral mechanism generate less and more distributed stress than an anterior connecting rod mechanism.…”
mentioning
confidence: 99%